PRINSIP HUKUM PERIMBANGAN DANA BAGI HASIL MINYAK DAN GAS BUMI - Indah Dwi Qurbani (Yuridika, 2014)
Based on Article 18 A (2) of the amended 1945 Constitution provisions, it can be inferred that article as the filosophical and constitutional basic of the Act No. 33 of 2004 about finance relationship between central government and regional government, include finance relationship in oil and gas sector. The problem statement in this research are firstly, elaborating of law oil and gas management in Indonesia and secondly analysing the principle of law distribution finance relationship between central government and regional government in sharing oil and gas finance. Social concept of ownership is a fundamental principle in the management of oil and gas as outlined in the basic orientation of national development. Oil and gas sector as a strategic non renewable natural resources shall be under the powers of the State and shall be used to the greatest benefit of the people.Keywords: principles of law, equity, production sharing, oil and gas